2017
DOI: 10.5222/j.child.2017.024
|View full text |Cite
|
Sign up to set email alerts
|

Prevelance of vitamin D and B12 deficiency in adolescence

Abstract: Amaç: D vitamininin kas-iskelet sistemi, immun sistem ve daha birçok mekanizma ile; B12 vitamininin ise özel-(1) , beslenme şekli ve besin özelliklerinin değişimi B12 eksikliğine neden olabilmektedir (2) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…For this reason, its deficiency is most frequently seen in the periods when the need is not adequately met with nutrients. Frequency of vitamin B12 deficiency in adolescents was reported to be %10.5 in our country (12). In our study, the median age of vitamin B12 deficient group was 13 years, and 27 of 34 patients (80%) were between the ages of 12 and 18 years that, they were in adolescence period likewise that study.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…For this reason, its deficiency is most frequently seen in the periods when the need is not adequately met with nutrients. Frequency of vitamin B12 deficiency in adolescents was reported to be %10.5 in our country (12). In our study, the median age of vitamin B12 deficient group was 13 years, and 27 of 34 patients (80%) were between the ages of 12 and 18 years that, they were in adolescence period likewise that study.…”
Section: Discussionsupporting
confidence: 54%
“…A total of 34 children (9 girls, 25 boys) with vitamin B12 deficiency and 36 healthy controls (17 girls, 19 boys) were analysed in the study. There was no difference between the groups in terms of median age [13 (range, 4-17) vs. 12.5 (range, [5][6][7][8][9][10][11][12][13][14][15][16][17]]. Physical examination was unremarkable in all subjects participated in…”
Section: Resultsmentioning
confidence: 98%
“…The results of this study were significant due to the high number of participants. In another study conducted by Yetim et al [10] , the rate of vitamin D deficiency in children older than 10 was reported as 56%.…”
Section: Discussionmentioning
confidence: 92%
“…[1] In recent studies conducted in Turkey, the prevalence of vitamin D deficiency has been reported from 16.5% to 89.6% (Table 4). [6][7][8][9][10][11][12][13][14][15][16][17] Among these studies, the highest rate of vitamin D deficiency was found in the study included pubertal children and adolescents. [11] The lowest deficiency rate was shown in a study conducted on children younger than 10 years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation